Lee Nukpe’s Nubile: A Carving With A Shadow - seid’ou, kari’kacha; Ampratwum, George; Kissiedu, Kwaku Boafo (Advances in Social Sciences Research Journal, 2020)
The Ghanaian sculptor Lee Nukpe belongs to the post-Independence or post-World War II generation of visual artists in Ghana whose bodies of work have not had due critical assessment, contextualization and review. The paper reviews Nukpe’s late-career work, Nubile, a bas relief representation of a bare-breasted young woman arrayed in Ghanaian nubility rites insignia. The authors identify carryovers from Ghana’s colonial and post-Independence generations such as the predominantly social realist aesthetic and veiled conservative sex and gender motifs. However, the authors also point out how the cut-and-dry cultural and formal motifs in Nubile are also undermined by Nukpe’s ostensible double-coding. This spectral feature of Nubile presents it as a “text with a shadow”. The authors argue that to a large extent, Nubile lends itself to ambivalent readings which could challenge Ghana’s patriarchal definitions of woman and nubility.